Ascorbic acid assisted bio-synthesis of Pd-Pt nanoflowers with enhanced electrochemical properties. (20th February 2017) - Odoom-Wubah, Tareque; Li, Zhenzhen; Lin, Zhou; Tang, Tingting; Sun, Daohua; Huang, Jiale; Li, Qingbiao
Highlights: Plant-mediated synthesis of porous Pd-Pt alloy NFs with dominant (111) planes. The biogenic Pd-Pt NFs were used directly in ethanol oxidation without special treatment. The PdPt3 NFs is 4.1, and 9.1 more active than commercial Pd and Pt–black toward ethanol oxidation. Electrocatalytic activity increased with Pt content, and stability with Pd addition Abstract: Bimetallic Pd-Pt nanoflowers (Pd-Pt NFs) of varying sizes (20–60 nm) were synthesized through the concurrent reduction of Pd(NO3 )2 and K2 PtCl4 using Cinnamomum camphora ( C. camphora ) leaf extract assisted by ascorbic acid (AA). C.Camphora acted as both a co-reducing agent and a green template in the synthesis protocol providing a fast, simple, green and cost-effective means of producing the Pd-Pt NFs. Characterization techniques such as X-ray diffraction (XRD), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS) were used to confirm the Pd-Pt NFs formation. FT-IR analysis showed that biomolecules such as polyphenols and flavonoids were responsible for the reduction while stretching vibration bands from CH, CC, OH, and CO O acted as capping agents. The as-formed Pd-Pt NFs showed excellent performance and stability in the electro-oxidation of ethanol in alkaline media. Electro-catalytic performance increased with Pt content, while addition of Pd increased stability. The PdPt3 NFs presented the best performance with a mass activity of 1.43 A mg −1 metal, 5.72, 4.93, 2.27, 1.27, 11 and 4.6% higher than the Pd, Pt, Pd3 Pt, and PdPt NFs, and commercial Pt and Pd-black respectively. However, it was more prone to poisoning, with an I f /I r value of 0.78 compared to 1.37 for Pd3 Pt NFs.